Avaliação dos efeitos de soluções alimentares e escovação na rugosidade de superfície, microdureza vickers e estabilidade de cor de uma cerâmica vítrea de dissilicato de lítio CAD/CAM - SILVA, Flávia Jucá Alencar e (2017)
Introduction. Lithium disilicate ceramics are widely used in aesthetic and functional restorations. Degradation of the material by factors present in the oral environment may interfere in a clinical performance. Objectives. To evaluate the effects of commonly consumed beverages and toothbrushing on surface roughness, microhardness and color stability of glazed and mechanic polished lithium disilicate ceramic CAD / CAM. Methods. 160 specimens of lithium disilicate ceramic were randomly distributed into two groups, according to surface preparation (n=80) - GG = glazed, GP = polished. Each group was randomly divided according to immersion solutions and toothbrushing (n=8) - AD (distilled water), AD+ESC (toothbrushing); CF (coffee), CF+ESC; CH (black tea), CH+ESC; VT (red wine), VT+ESC; CC (cola refrigerant), CC+ESC. The surface properties were evaluated before (T0) and after (T1) immersion in beverages and toothbrushing simulated 5 years. Results. There was an increase in roughness after immersion in the glazed ceramics, being significant in CF (p = 0.03) and CH (p = 0.004). The ΔRa value was higher in the GG groups (p=0.027), with highest increase in CH group (p=0.003). All beverages caused reduction of ceramic hardness in GG and GP groups. In GG groups, the reduction was significant in CF (p=0.001), CH (p=0.005) and VT groups (p=0.031). In GP groups, the reduction was significant for all solutions. Color changes were observed in all immersion groups, with highest staining caused by VT (GG: ΔE = 2.6, p <0.001 and GP: ΔE = 2.22, p = 0.004). The effect of each beverage on the ceramic color stability was similar, regardless type of surface preparation (p=0.729). The toothbrushing test after immersions did not significantly modify alteration caused by beverages tested in all evaluated properties, regardless surface preparation in the same period. Conclusion. Immersion in the solutions causes changes in properties tested on lithium disilicate ceramics to be glazed or polished. Toothrushing was not able to potentiate or reduce the alterations found. Mecanic polishing has potential to protect the ceramics from the deleterious effects of tested beverages and toothbrushing similar to glaze.